(untitled) (Universal International Scientific Journal, 2026)
This article identifies the complexities of ensuring quality in the context of the widespread penetration of digital technologies into education. The problem is seen at the intersection of teaching content, assessment reliability, academic integrity, pedagogical competence, and infrastructure imbalances. The analysis is conducted through the “input–process–output” model of educational quality. As an innovation, a conceptual explanation is provided that links the factors that reduce quality to management decisions.